Episteme of Endurance: Anandâ€™s Primal Motivations in Untouchable - Singh, Osmania University, Hyderabad, India, Sukhbir (Asiatic: IIUM Journal of English Language and Literature, 2007)
Mulk Raj Anandâ€™sÂ UntouchableÂ (1935) has commonly been examined in the light of the Hindu caste system in India, and the novelâ€™s protagonist Bakha has customarily been treated as a victim of the upper class Hindus for his birth in an untouchable community. Written much earlier to the Second World War and Indiaâ€™s independence in 1947,UntouchableÂ still remains popular with present readers due to the never abating caste politics in post-independence India. Hence, most critics gloss the sad plight of Bakha under a â€œpolitically correctâ€ perspective to arouse sympathy for the lower caste community, generate a gruelling sense of guilt among the high caste Hindus, and solicit justice for the untouchables from the beneficiaries of the caste system. Intoxicated with empathy for the poor, these commentators blissfully overlook the implicit authorial intention in the novel. A re-reading ofÂ UntouchableÂ in view of the post-war extremity theories indicates that Anand endeavours more to extricate the lower caste people from their inferiority complex with a bold projection of Bakha than to merely expose the pathetic nature of their predicament under the high caste Hindu dominance. This paper attempts to analyse Bakhaâ€™s primal potentials in the light of the protective manoeuvres later made by protagonists in several post-war European and American novels while facing similar inhuman circumstances. Thereby, the paper reassesses the character of Bakha through a close consideration of his instinctive responses for endurance in the context of survival strategies later employed by protagonists in the post-war fictions of extremity.